A virtual-physical collision detection interface for AR-based interactive teaching of robot. (August 2020) - Chen, Chengjun; Pan, Yong; Li, Dongnian; Zhang, Shilei; Zhao, Zhengxu; Hong, Jun
Abstract: At present, online lead-through and offline programming methods are widely used in programming of industrial robots. However, both methods have some drawbacks for unskilled shopworkers. This paper presents an Augmented Reality (AR)-based interactive robot teaching programming system, which virtually projected the robot onto the physical industrial environment. The unskilled shopworkers can use Handheld Teaching Device (HTD) to move end-effector of virtual robot to follow endpoint of the HTD. In this way, the path of the virtual robot can be planned or tested interactively. In addition, collisions detection between virtual robot and physical environment is key to test the feasibility of robot path. So, a method for detecting virtual-physical collisions is presented in this paper by comparing the depth values of corresponding pixels in depth image acquired by Kinect and computer-generated image in order to get collision-free paths of the virtual robot. The Quadtree model is used to accelerate the collision detection process and get distance between virtual model and physical environment. Using the AR-based interactive robot teaching programming system presented in this paper, all workers even unskilled ones in robot programming, can quickly and effectively get the collision-free robot path.